Plasmonic Au nanoclusters dispersed in nitrogen-doped graphene as a robust photocatalyst for light-to-hydrogen conversion. Issue 40 (31st August 2021) - Van Dao, Dung; Cipriano, Luis A.; Di Liberto, Giovanni; Nguyen, Thuy T. D.; Ki, Sang-Woo; Son, Hoki; Kim, Gyu-Cheol; Lee, Kang Hyun; Yang, Jin-Kyu; Yu, Yeon-Tae; Pacchioni, Gianfranco; Lee, In-Hwan
Abstract : Au nanoclusters (2.18 wt%) consisting of a few tens of atoms supported nitrogen-doped graphene deliver an impressive hydrogen evolution reaction rate of 3.16 μmol mgcat −1 h −1 under visible-light irradiation and a high maximum quantum yield of 14.3%. Abstract : Supported plasmonic Au nanoclusters (NCs) consisting of a few tens of atoms can potentially offer great advantages for the light-driven hydrogen evolution reaction (HER). Here, we report on the synthesis of well-dispersed and stable plasmonic Au NCs of 0.5–1.0 nm size on nitrogen-doped high surface area graphene (N-Gr) via freeze-drying and pyrolyzing in argon. The Au NCs/N-Gr photocatalyst exhibits under visible-light an impressive HER achievement (3.16 μmol mgcat −1 h −1 ) compared to Au single atoms/N-Gr (2.06 μmol mgcat −1 h −1 ) and Au nanoparticles (20 nm size)/N-Gr (0.92 μmol mgcat −1 h −1 ), with a maximum apparent quantum yield of 14.30%. These performances are synergistically attributed to two effects: (a) the strong surface plasmon resonance stimulated by light absorption and transferred near the surface of Au NCs, where the N-Gr conductive support can prolong the plasmon-produced hot electrons and direct the light-to-hydrogen conversion; (b) a high catalytic efficiency of Au NCs/N-Gr nanocomposites.